Outcomes of Anticoagulant Therapy with Low-Molecular-Weight Heparin (LMWH) and Warfarin for Thromboangiitis Obliterans (TAO) - Gao, Jiangping; Huang, Liuhuan; Wang, Jianli (Current Vascular Pharmacology, 2021)
Background: Thromboangiitis obliterans (TAO) is a chronic, non-atherosclerotic, progressive inflammatory vascular disease affecting the small- and medium-size arteries and veins of the extremities. Objective: To evaluate whether long-term anticoagulation with low-molecular-weight heparin (LMWH) and warfarin is beneficial for treating the inflammation and symptoms associated with TAO. Methods: Patients with TAO who underwent anticoagulation as the mainstay of treatment were included in this prospective study. Rest pain relief and healing of trophic lesions (as the primary and secondary endpoint) were investigated at Day 14 and after 6 months of follow-up. High sensitivity C-reactive protein (hsCRP), monocyte count, and ankle-brachial index (ABI) were recorded, and the difference was compared before and after 2-week anticoagulation. The Chi-square test was used to compare the difference between anticoagulant and aspirin groups (based on the literature). Results: From 2014 to 2019, 18 patients were included. Only 1 patient with wet gangrene received endo-therapy for a failing stent at the start of treatment. After 14 days, 12 of 13 (92%) patients showed complete ulcer healing, and 17 of 18 (94%) patients showed complete relief from rest pain. Monocyte-counts and hsCRP levels decreased significantly (p<0.001) after a 2-week period of anticoagulation with LMWH. The mean follow-up was 2.6 years (range 0.5-5 years). At 6 months, all patients showed relief of rest pain and complete healing of trophic lesions. All endpoints were significantly improved compared with the aspirin group (p<0.01), and no rest pain or ulcer/gangrene recurred during follow-up. Conclusion: Anticoagulant therapy may alleviate the inflammation and symptoms of TAO.
Keywords: high-sensitivity C-reactive protein